Analysis of Water Consumption in the Context of Public Health and Economics: The Case of Ankara - Güner, Ümit; Pamuk, Rifat; Aksoy, Şemsi Mustafa (My University, 2023)
This study aims to examine water consumption, which is the most basic necessity of people, within the framework of public health and economics. While water is an important economic research topic because it is the most important and most widely used economic good, it is also one of the most common medical research topics in the context of public health since it is consumed by all individuals of all societies. The use of packaged water in places where healthy tap water is inaccessible has positive effects on public health. On the other hand, the use of unnecessary packaged water is a very important public health problem in today's global world as it means more plastic waste. In our study, one of the most important variables affecting the consumption of packaged water, the parameter of trust in tap water, was analysed in Ankara by associating it with the concept of income level. As a result of the statistical analyses, it was determined that there was no statistical relationship between the income level with the use of packaged water and trust in tap water variables. In addition, it has been determined that there is a negative relationship between trust in tap water and packaging water usage variable. This result refuted the established claims that income level is the main determinant of water consumption preference.
Keywords: Water; Public Health; Consumption; Income